2002
DOI: 10.1097/00002508-200211001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Botulinum Toxins: Background and History

Abstract: The seven botulinum neurotoxin serotypes share less than 50% sequence homology and are immunologically distinct. The neurotoxins inhibit release of the neurotransmitter acetylcholine from the axon terminals of motor neurons, preganglionic sympathetic and parasympathetic neurons, and postganglionic parasympathetic nerves by a multi-step mechanism that differs slightly, but significantly, for each serotype. The inhibition is long lasting but temporary. The resulting muscle paralysis has provided the basis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 42 publications
1
86
0
5
Order By: Relevance
“…This toxin blocks the release of acetylcholine at the axon terminal (Setler, 2002) Its intramuscular application has proven to be relatively safe (Bakheit, 2006), but it is not free of adverse effects, such as blocking of autonomic nerves, muscle atrophy by anatomical denervation and immunological reactions (Simpson et al, 2009;Dressler and Hallett, 2006) The occurrence of side effects is dependent on the delivered dose of toxin (Borodic et al, 1990;Eleopra et al, 1996). It has been clinically shown that injection of a minimum effective dose reduces the presence of adverse effects (Brans et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This toxin blocks the release of acetylcholine at the axon terminal (Setler, 2002) Its intramuscular application has proven to be relatively safe (Bakheit, 2006), but it is not free of adverse effects, such as blocking of autonomic nerves, muscle atrophy by anatomical denervation and immunological reactions (Simpson et al, 2009;Dressler and Hallett, 2006) The occurrence of side effects is dependent on the delivered dose of toxin (Borodic et al, 1990;Eleopra et al, 1996). It has been clinically shown that injection of a minimum effective dose reduces the presence of adverse effects (Brans et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum A toxin is known to exert its effect by reducing the rate of supply of readily releasable neurotransmitters. 8,16,17 This chemical denervation results in the atrophy of the affected muscle. This chemodenervation effect is temporary, so the safety and convenience of botulinum A toxin enable it to be used for various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sub-optimal environmental [24,25] and complications [26] associated with their use may factors such as temperature, humidity, and wind will be found be found in the literature, denature these proteins, thereby reducing their effectiveness. Exposure to air, or direct sunlight, will denature the toxin As Biological Warfare Agents within a few hours, rendering it biologically inactive [3].…”
Section: )mentioning
confidence: 99%